Proanthocyanidins extracted from grape seeds inhibit the growth of hepatocellular carcinoma cells and induce apoptosis through the MAPK/AKT pathway. (February 2022) - Zheng, Wancai; Feng, Yujing; Bai, Yujia; Feng, Zuoshan; Yang, Xijuan; Dang, Bin; Xiao, Ming; Zhang, Jianmei; Han, Sheng-Qiang
Abstract: Proanthocyanidins naturally occur in various fruits, some vegetables and beverages. Increasing evidence has shown that dietary intake of proanthocyanidins is a promising alternative to tumor chemoprevention or chemotherapy. Grape seeds are the most abundant source of proanthocyanidins, and grape seed proanthocyanidins (GSPs) show an anticancer effect on hepatocellular carcinoma (HCC), which accounts for approximately 85–90% of all primary liver malignancies. Although an increasing number of studies have investigated the effects of GSPs on HCC and the associated mechanisms, the precise mechanism of GSP therapy in HCC remains unclear. This study aimed to understand the cytotoxic effect of GSPs on HepG2 cells by investigating morphology and growth inhibition. Cell proliferation and apoptosis were estimated by an MTT assay and flow cytometry, and the protein expression of HepG2 cells was determined through Western blotting. The results indicated that GSPs could markedly inhibit HepG2 liver cancer cells and induce apoptosis, with the effects varying by dose and treatment time. Furthermore, GSPs inhibited the phosphorylation of extracellular regulated protein kinases (ERK), c-Jun NH2 -terminal kinase (JNK), p38 mitogen-activated protein kinase (p38 MAPK), IκBα, pyruvate dehydrogenase kinase 1 (PDK1), glycogen synthase kinase-3 beta (GSK3β) and protein kinase B (AKT), which accounted for the inactivation of mitogen-activated protein kinase/AKT (MAPK/AKT) pathways. These results indicate that GSPs are a potential source of natural chemopreventive agents for the treatment of HCC. Graphical abstract: Image 1